Instrumentalizing Ta'abbudiyyah for Political Legitimacy: A Maqasid al-Shari'ah Critique - Rifai Umaaya; Afin Rumbia; Ilham Syarif Hidayatullah (Pustaka Peradaban, 2026)
Religious symbols increasingly play a significant role in constructing political legitimacy, yet limited attention has been given to the normative implications of the political instrumentalization of ta'abbudiyyah from the perspective of maqasid al-shari'ah. This article analyzes how ta'abbudiyyah, originally understood as sincere devotion to Allah, is transformed into a symbolic resource for political legitimacy and develops a maqasid al-shari'ah-based framework for evaluating this phenomenon. Employing a qualitative normative-conceptual approach based on library research, the study draws upon classical works of fiqh, usul al-fiqh, and maqasid al-shari'ah, complemented by contemporary literature on the sociology of religion and political legitimacy. The findings demonstrate that the political instrumentalization of ta'abbudiyyah operates through interconnected mechanisms of desacralization, the commodification of worship symbols, the naturalization of piety discourse, and the conversion of symbolic capital into political legitimacy. From the perspective of maqasid al-shari'ah, these mechanisms have the potential to undermine the preservation of religion (hifz al-din), intellect (hifz al-'aql), life (hifz al-nafs), and wealth (hifz al-mal), thereby supporting the preventive application of sadd al-dhara'i'. This study contributes to contemporary Islamic legal scholarship by proposing a normative analytical framework that distinguishes the legitimate role of religion in politics from the political instrumentalization of ta'abbudiyyah for image-building and political legitimacy. Simbol-simbol keagamaan semakin memainkan peran penting dalam mengonstruksi legitimasi politik, namun perhatian terhadap implikasi normatif dari instrumentalisi politik ta’abbudiyyah dari perspektif maqasid al-shari’ah masih relatif terbatas. Artikel ini menganalisis bagaimana ta’abbudiyyah, yang pada mulanya dipahami sebagai pengabdian tulus kepada Allah, ditransformasikan menjadi sumber daya simbolis untuk legitimasi politik, sekaligus mengembangkan kerangka kerja berbasis maqasid al-shari’ah untuk mengevaluasi fenomena tersebut. Menggunakan pendekatan kualitatif normatif-konseptual berbasis studi pustaka, penelitian ini mengandalkan karya-karya klasik fiqh, usul al-fiqh, dan maqasid al-shari’ah, yang dilengkapi dengan literatur kontemporer tentang sosiologi agama dan legitimasi politik. Temuan penelitian menunjukkan bahwa instrumentalisi politik ta’abbudiyyah bekerja melalui empat mekanisme yang saling terhubung: desakralisasi dan komodifikasi simbol-simbol ibadah, naturalisasi wacana kesalehan, serta konversi modal simbolis menjadi legitimasi politik. Dari perspektif maqasid al-shari’ah, mekanisme-mekanisme ini berisiko mengikis pemeliharaan agama (hifz al-din), akal (hifz al-'aql), jiwa (hifz al-nafs), dan harta (hifz al-mal), sehingga membenarkan penerapan prinsip pencegahan sadd al-dhara'i'. Studi ini berkontribusi pada kajian hukum Islam kontemporer dengan menawarkan kerangka kerja evaluatif yang membedakan antara keterlibatan agama yang autentik dalam politik dengan manipulasi instrumental ibadah untuk pencitraan politik.